SCAPS numerical analysis of solid-state dye-sensitized solar cell utilizing copper (I) iodide as hole transport layer - Arith, Faiz; Noorasid, Nur Syamimi; Firhat, Ain Yasmin; Mustafa, Ahmad Nizamuddin; Mohd Shah, Ahmad Syahiman (Chulalongkorn University, Bangkok, Thailand, 2022)
Here, numerical study of solid-state dye-sensitized solar cell (SSDSSC) with Copper (I) Iodide as a hole transport layer was investigated using SCAPS-1D simulation software. The complete simulated device structures in this project are composed of FTO/TiO2/N719/CuI/Ni. Several key parameters of HTL such as layer thickness, doping concentration, working temperature, and interface defect have been analysed to obtain the highest efficiency for SSDSSC as well as the influence of back contact. The incorporation with various ETLs such as TiO2, ZnO, and SnO2 were also studied. The results show that SSDSSC with back contact yields a better performance due to low HTL thickness compared to without back contact. In addition, it can also be proved that TiO2 as ETL obtained the best efficiency up to 5.6%. Further investigation also found that combining optimized CuI and TiO2 parameters with a perovskite layer would increase cell efficiency to nearly 30%, higher than previously reported devices. The proposed parameter structure may trigger the temptation for the use of CuI as HTL in solar cell application.